The effects of flow pulses on river plumes in the Yellow River Estuary, in spring. Issue 1 (9th November 2022) - Fan, Yaoshen; Zhang, Shaohua; Du, Xiaokang; Wang, Guangzhou; Yu, Shoubing; Dou, Shentang; Chen, Shenliang; Ji, Hongyu; Li, Ping; Liu, Fucheng
Abstract: In this paper, an extended three-dimensional (3D) model of the Yellow River Estuary (YRE) is established. It is based on a Delft 3D shallow-water high-resolution hydrodynamic model. The model is calibrated and verified by field observation data, which ensures its stability and accuracy, and provides a better simulation of the river plume in the estuary under different flow inputs. Since 2009, the spring flow pulse of the Yellow River can be divided into four types. The strong flow pulse is more conducive to the extension of the low salinity zone (LSZ). Doubling the peak discharge of pulse flow increases the LSZ area by 60%. The retardation time of salinity change in response to the flow pulse in estuary waters is weakly affected by the flow pulse intensity. The difference in shear front between the spring tide and the neap tide is the main dynamic mechanism contributing to the different retardation times. The average retardation time is 73 h during the spring tide and 55 h during the neap tide. In order to reduce the estuary salinity, it is suggested that the optimal time for the peak value of flow pulse in the river mouth is during the neap tide. HIGHLIGHTS: An extended three-dimensional (3D) model of the Yellow River is established based on a Delft 3D shallow-water high-resolution hydrodynamic model. The study focused on the change process of salinity distribution in the Yellow River Estuary under different discharge conditions. The retardation time of salinity change in response to the flow pulse in estuary waters is affected by the flow pulse intensity.